LANGUAGE FUNCTIONS USED BY THE CARETAKERS OF AUTISTIC CHILDREN IN âMIRACLE RUNâ - Degaf, Adwin (Universitas PGRI Yogyakarta, 2014)
Abstract This study investigates language functions used by the caretakers of autistic children in âMiracle Runâ. The objectives of the study are to find out the kinds and the effectiveness of language functions used by caretakers in the film. This study uses descriptive qualitative approach. It is categorized as discourse analysis because this study analyzes phenomena of talk in interaction. The data are collected from the utterances used by the caretakers; they are mother, doctor, teacher, and therapist when talk to the autistic children and those are analyzed by using M.A.K Halliday theory on language functions. Key words: Language Functions, Caretaker Speech, Autistic Children.